2022
DOI: 10.1186/s12909-022-03718-8
|View full text |Cite
|
Sign up to set email alerts
|

Using social prescribing by Iranian medical students: a step towards community-orientation and social determinants of health by revising the health internship curriculum

Abstract: Background In order to meet patients' social needs, including social prescribing in the curriculum of medical students is a necessity. Aim Becoming familiarized with the SDH perspective and referral method to link workers (LWs) and the principles of social prescribing (SP). Methods Using Levin's model, the intervention was performed in the field of health of medical students in 2018–2020 for 38 interns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…Experiences in other countries reveal that student-led efforts to educate peers about social prescribing need to be supplemented with formal education through a combination of didactic teaching and experiential learning opportunities. 4,[21][22][23][24][25] Together, these actions will help to build the social prescribing student movement, which will not only shape the wider social prescribing movement, but also the future of our health system.…”
Section: A Call To Actionmentioning
confidence: 99%
“…Experiences in other countries reveal that student-led efforts to educate peers about social prescribing need to be supplemented with formal education through a combination of didactic teaching and experiential learning opportunities. 4,[21][22][23][24][25] Together, these actions will help to build the social prescribing student movement, which will not only shape the wider social prescribing movement, but also the future of our health system.…”
Section: A Call To Actionmentioning
confidence: 99%
“…This study concluded that similar to a lot of efforts that have been made in western countries to revise the curriculum of medical students in line with changes, demographic needs and technology progressions, an evolution of medical education is also needed in Iran. This study also resulted that enrichment of medical education with social prescription is the gateway toward strengthening of primary health care [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Selon ce que nous avons observé dans d'autres pays, les efforts déployés par les étudiants pour sensibiliser leurs pairs à la prescription sociale doivent être renforcés par une éducation formelle qui allie l'enseignement didactique aux possibilités d'apprentissage par l'expérience4,[21][22][23][24][25] .Ensemble, ces mesures vont aider à créer un mouvement étudiant pour la prescription sociale qui façonnera non seulement le mouvement pour la prescription sociale en général mais aussi l'avenir de notre système de santé.…”
unclassified